Critical theory and methodology - Morrow, Raymond Allen; Brown, David D., 1954-; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1994)
Raymond Morrow's book traces the history and outlines the major tenets of critical theory for an undergraduate audience. He exemplifies the theory through an analysis of two leading social theorists: Jurgen Habermas and Anthony Giddens. Specific to this volume is the emphasis on the link between critical theory and empirical research and social science methodology, often thought to be incompatible.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Critical theory; Social sciences -- Philosophy; Sociology -- Methodology; Electronic books